Sistem Informasi Arsip Surat Masuk dan Keluar Berbasis Website Disdukcapil Nias - Sofe Priaman Mendrofa; Sinar Elsa Zendrato; Aris Gunawan Zai; Elviani Gea; Ikhtiar Mudah S. Zendrato; Melianus Zebua; Nov Elhan Gea (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
Manual management of letter archives in government agencies remains a barrier to efficient administrative services. The main problems faced are delays in document retrieval, the risk of losing physical archives, and the lack of a tracking system and data integration between departments. This study aims to develop a website-based information system for incoming and outgoing letter archives at the Population and Civil Registration Office (Disdukcapil) of Nias Regency. This system is designed to replace manual processes and improve the effectiveness of agency archive management. The method used is the Waterfall software development model, with stages of needs analysis, system design, implementation, testing, and maintenance. Data collection techniques were carried out through direct field observation, interviews with related employees, and literature studies relevant to digital archiving systems. Analysis was carried out on user needs, business processes for letter management, and testing of the developed system's functionality. The results of the study indicate that this system can speed up the process of recording and tracking letters by up to 50%, reduce the risk of document loss, and improve data accuracy and transparency of disposition. With classified login features, automatic notifications, and digital reporting, this system is considered effective in supporting administrative modernization. The system developed also has the potential to be replicated in other government agencies to encourage digital transformation in public services.